Systematic Review and Meta-Analysis of the Incidence of Chronic Kidney Disease After Pediatric Critical Illness - Olugbenga Akinkugbe, MBBS, MA, MRCPCH; Luca Marchetto, MD, PhD; Isaac Martin, MBBS, MD(Res), MRCPCH; Shin Hann Chia, MBBS, FRCA (Critical Care Explorations)
OBJECTIVE:. Survivors of pediatric critical illnesses are at risk of significant long-term organ sequelae. Chronic kidney disease (CKD) is a complication of critical illness (and ICU interventions) associated with growth impairment, cardiovascular disease, and early death. Our objective was to synthesize the evidence on the incidence of CKD among survivors of pediatric critical illness. DATA SOURCES:. MEDLINE, Embase, Cumulative Index to Nursing and Allied Health Literature, and Cochrane Register of Controlled Trials from inception to February 2024. STUDY SELECTION:. Observational studies reporting the incidence of de novo CKD among survivors of pediatric critical illness. DATA EXTRACTION:. Two reviewers independently extracted data on study design, setting, population, demographics, diagnostic criteria, and outcome. DATA SYNTHESIS:. Meta-analysis was used to describe the incidence of CKD among survivors, risk of bias (RoB) assessed using the Joanna Briggs Institute Tool, and strength and reliability of evidence assessed with GRADE (Grading of Recommendations, Assessment, Development, and Evaluations). CKD was quantified as an estimated glomerular filtration rate (eGFR) less than 90 mL/min/1.73 m2 (outcome 1), eGFR less than 60 mL/min/1.73 m2 (outcome 2), and end-stage renal disease (ESRD) as eGFR less than 15 mL/min per 1.73 m2 (outcome 3). Twelve studies (3642 patients) met selection criteria and reported at least one measure of CKD. The median duration of follow-up was 2, 3.6, and 5 years, respectively, for outcomes 1, 2, and 3. For each threshold, the pooled estimate of CKD incidence was 24% (95% CI, 16–32%) for eGFR less than 90, 14% (95% CI, 6–23%) less than 60, and 4% (95% CI, 0–7%) for ESRD. The overall quality assessment indicated a moderate RoB. CONCLUSIONS:. Among a heterogenous population of pediatric critical illness survivors, an important minority of survivors developed CKD or ESRD. This study highlights the importance of diagnostic criteria for reporting, a greater focus on postcritical care surveillance and follow-up to identify those with CKD. Further study would facilitate the delineation of high-risk groups and strategies for improved outcomes.